Consumer Perception and Challenges of Halal Certification in the Food and Beverage Industry in Indonesia - Magfiratun, Siti; Mujibatun, Siti; Imron, Ali (International Journal of Nusantara Islam, 2025)
Halal certification in the food and beverage industry represents a complex multidimensional ecosystem in Indonesia, encompassing consumer perceptions, regulatory challenges, and strategic economic implications. This comprehensive library research explores the intricate dynamics of halal certification through a systematic analysis of contemporary scientific literature published between 2019-2024. Utilizing content and comparative analysis methods, the study investigates consumer awareness, regulatory frameworks, economic dimensions, and technological transformations in halal certification. Research findings reveal significant consumer awareness, with 87.2% of Muslim consumers considering halal certification a primary product selection criterion. The study identifies structural challenges in regulatory implementation, methodological complexities in verification processes, and the strategic economic potential of halal-certified products. Technological information platforms emerge as crucial mechanisms for enhancing transparency and accountability. The research recommends a holistic, collaborative approach integrating perspectives from religious scholars, food technologists, and management experts to develop a credible, sustainable halal certification ecosystem.